Management of kidney transplant recipients for primary care practitioners - Manal Alotaibi; Brandon Trollinger; Sam Kant (BMC Nephrology, 2024)
Abstract Patients with kidney transplants have a significant co-morbidity index, due to a high number of pre-existing conditions and use of immunosuppression medications. These patients are at higher risk of developing conditions such as hypertension, dyslipidemia, post-transplant diabetes, cardiovascular events, and anemia. Moreover, they are particularly susceptible to infections such as urinary tract infections or pyelonephritis, cancers, and gastrointestinal complications such as diarrhea, which in turn may be attributed to medication adverse effects or infectious causes. Along with these concerns, meticulous management of electrolytes and allograft function is essential. Prior to prescribing any new medications, it is imperative to exercise caution in identifying potential interactions with immunosuppression drugs. This review aims to equip primary care practitioners to address these complex issues and appropriate methods of delivering care to this rapidly growing highly susceptible group.